Sialic Acid Metabolism: A Key Player in Breast Cancer Metastasis Revealed by Metabolomics - Teoh, Shao Thing; Ogrodzinski, Martin P.; Ross, Christina; Hunter, Kent W.; Lunt, Sophia Y. (Frontiers in Oncology, 2018)
Metastatic breast cancer is currently incurable. It has recently emerged that different metabolic pathways support metastatic breast cancer. To further uncover metabolic pathways enabling breast cancer metastasis, we investigated metabolic differences in mouse tumors of differing metastatic propensities using mass spectrometry-based metabolomics. We found that sialic acid metabolism is upregulated in highly metastatic breast tumors. Knocking out a key gene in sialic acid metabolism, Cmas, inhibits synthesis of the activated form of sialic acid, cytidine monophosphate-sialic acid, and decreases the formation of lung metastases in vivo. Thus, the sialic acid pathway may be a new target against metastatic breast cancer.